THE INFLUENCE OF ACEHNESE CULTURAL VISUAL MEDIA ON ELEMENTARY SCHOOL STUDENTS’ ABILITY TO WRITE NARRATIVE PARAGRAPHS - Arviani, Venni; Novianti, Novianti (CV Naskah Aceh, 2025)
Writing skills are a fundamental competency in Indonesian language learning at the elementary school level, particularly in narrative paragraph writing. However, many students still face challenges in developing ideas, structuring storylines, and selecting appropriate vocabulary. This study aims to determine the influence of Acehnese culture-based visual media on students’ narrative writing skills. The research used a pre-experimental one-group pretest-posttest design involving 26 fourth-grade students of UPTD SD Negeri 2 Kuala. A narrative writing test was administered before and after the intervention, and the data were analyzed using a Paired Sample t-Test. The results show a significant influence of Acehnese culture-based visual media on students’ writing performance. The mean posttest score exceeded the pretest score by 6.727 points. Statistical analysis confirmed this improvement with t = -8.360, df = 25, and Sig. (2-tailed) = 0.000 < 0.05. These findings indicate that the use of such media helps students better organize storylines, generate ideas, and remain motivated in writing activities. In conclusion, Acehnese culture-based visual media has a positive influence on students’ narrative paragraph writing skills. Beyond language improvement, it also fosters appreciation of local culture, making the learning process more meaningful and contextually relevant.